Estudio sobre los procedimientos de identificación del trastorno específico del lenguaje - Vera, Jesús; Sánchez, Berta; Rodríguez, Juana (Revista de Investigación en Logopedia, 2012)
The procedures of studying and treating the Specific Language Impairment (SLI) are aspects still poorly understood mainly due to a number of factors some of them related to the circumstance of no reaching a consensus of its nature, a wide range of different professionals trying to analyze the SLI from a markedly distant perspectives such as the clinical or experimental ones and a rich and sometimes contradictory literature concerned. The objectives in this study were: a) to characterize the type of professionals in our environment trying to identify and treating the SLI; b) to know the conceptualization those professionals make on SLI c) to research on the different procedures of identifying SLI in relation to current theoretical models. Through a survey conducted we have obtained results which allow us to state that there is a wide range of professionals in addressing the SLI in our cultural environment, that there is not a sufficient degree of consensus neither on the characterization of the disorder nor on the diagnostic procedures used and that the diagnoses of the professionals mentioned do not respond to the three basic criteria currently used in the identification of SLI: discrepancy, specificity and risk markers.